1938
DOI: 10.1017/s0022172400032617
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of factors governing potato-starch refection in rats

Abstract: No accepted or acceptable explanation of the phenomenon has yet been put forward. It has been suggested by the various authors and particularly by Fridericia et al. (1927) that bacterial synthesis of vitamin B in the intestine of the rat may be the explanation of the condition. Schieblich & Rodenkirchen (1929) have described a “vibrio-like” organism which they claim to be responsible for refection, but this finding has so far not been confirmed. In a recent dissertation on refection Nathan (1935) believes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

1949
1949
1966
1966

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Infection through association either in nature or in the cage occurs by fecal contamination of food or water or by ingestion of feces. The coprophagic habit in rats has been recognized ( 17,42) and would appear to make the elimination of Giardia from rats by the use of self-cleaning cages(3 1) a very uncertain undertaking. The author's observations indicate coprophagy to be a more common habit for hamsters than rats.…”
Section: Methods and Ecologymentioning
confidence: 99%
“…Infection through association either in nature or in the cage occurs by fecal contamination of food or water or by ingestion of feces. The coprophagic habit in rats has been recognized ( 17,42) and would appear to make the elimination of Giardia from rats by the use of self-cleaning cages(3 1) a very uncertain undertaking. The author's observations indicate coprophagy to be a more common habit for hamsters than rats.…”
Section: Methods and Ecologymentioning
confidence: 99%
“…The rate of growth of the animals was considerably retarded on the potato-starch diet. This particular starch has been used extensively in producing refection in rats (Kon, Kon & Mattick, 1938;Kon, 1945). We happened to have a quantity of potato1starch available and since no report could be found of its use in an experimental investigation of caries it was of interest to study the effect of this starch on the incidence of dental caries.…”
mentioning
confidence: 99%
“…Thus either the total amount of vitamins synthesized must be greater in the refected than in the normal rat or the efficiency of utilization must be higher or, more probably, both. Kon, Kon & Mattick (1938) suggested that the presence of undigested starch in the caecum of the refected rat, along with the requisite starch-splitting enzymes led to a vigorous fermentation and a resulting acid pH that created conditions favourable for both vitamin synthesis and absorption.During recent years the effect of sulphonamides on the synthetic activities of intestinal micro-organisms has been extensively studied, and muchvaluable information 1946), who found that sulphonamides depressed the growth rate of the rats and their faecal excretion of both vitamins. Untreated refected rats excreted no measurable amounts of thiamine in the urine, whereas their urinary excretion of riboflavin was comparable with that of stock rats.…”
mentioning
confidence: 99%
“…Thus either the total amount of vitamins synthesized must be greater in the refected than in the normal rat or the efficiency of utilization must be higher or, more probably, both. Kon, Kon & Mattick (1938) suggested that the presence of undigested starch in the caecum of the refected rat, along with the requisite starch-splitting enzymes led to a vigorous fermentation and a resulting acid pH that created conditions favourable for both vitamin synthesis and absorption.…”
mentioning
confidence: 99%